KEANEKARAGAMAN JENIS ROTAN DI KAWASAN HUTAN ADAT SEPORA DESA KASROMEGO KECAMATAN BEDUAI KABUPATEN SANGGAU - Rentiria, Mismeka; Manurung, Togar Fernando; Yani, Ahmad (JURNAL HUTAN LESTARI, 2016)
In the wood is complex structure creates an environment that is, allowing the diversity and plants to live within. One of the diversity that can grow in the woods Indonesia is rattan. Wicker including the typical tropical belonging to the family palmae (Dransfield and Manokaran 1996 in Jumiati et al, 2012). In the woods customary Sepora there have been a number of rattan. It can be seen from surrounding the use of these plants as the rattan, wicker rattan, mat, wicker vegetables, basket, the material and forth. The types of rattan is in an area of forest customary Sepora had not yet been attention so that infomation about the types of rattan not yet avaible. The purpose of this study is to find the diversity of spesies in the industry, wicker especially a kind of which is generally usedby the community and rattan supplies as feedstocks. Of the field observation finding of rattan derived of the genus, calamus, korthalsia and daemonorops. Of the six flavors of the raw materials only one kind of rattan a solitary namely of the genus calamus. Based on analysis obtained diversity field index to spesies (HÊ¹) ranges from 0,0642-0,1530, or less than one which means that the diversity of the species in this area relatively low. While the dominant index value (C) of 0,0024-0,0708, or less than one showing that the absence of distinction from one species with other species within to community, to achieve that in a community has an equal chance of good growing. Keyword: Diversity, species of rattan, indigenous forest.